2022
DOI: 10.1681/asn.2022030323
|View full text |Cite|
|
Sign up to set email alerts
|

Sex Differences in Age-Related Loss of Kidney Function

Abstract: BackgroundCKD is more prevalent in women, but more men receive kidney replacement therapy for kidney failure. This apparent contradiction is not well understood.MethodsWe investigated sex differences in the loss of kidney function and whether any sex disparities could be explained by comorbidity or CKD risk factors. In the Renal Iohexol Clearance Survey (RENIS) in northern Europe, we recruited 1837 persons (53% women, aged 50–62 years) representative of the general population and without self-reported diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…In contrast, female gender was associated with lower SHAP values and decreased risks of developing ESRD. A previous study also found that renal function decline in women was slower compared to men among middle-aged and elderly individuals [51].…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, female gender was associated with lower SHAP values and decreased risks of developing ESRD. A previous study also found that renal function decline in women was slower compared to men among middle-aged and elderly individuals [51].…”
Section: Discussionmentioning
confidence: 81%
“…It has been known for 30 years that in experimental models, the male gender enhances the age-related decline in renal function ( Bolignano et al, 2014 ). In a recently published study on sex differences in the loss of kidney function, it was reported that in the general population without major chronic diseases or risk factors for CKD, women exhibited a slower mean GFR decline rate than did men ( Melsom et al, 2022 ). Considering the different genotypes, age-associated renal damage in the glomeruli and tubules increases significantly in male RAGE-KO animals, which is significant when compared with wild-type male mice and also with female RAGE-KO.…”
Section: Resultsmentioning
confidence: 99%
“…Crude incidence rates of adverse outcomes were generally higher among men aged 18-39 years, while adjusted hazard ratios for each outcome were generally higher among women. Previous epidemiological studies, including analyses of data from the Chronic Renal Insufficiency Cohort in the US54 and the Renal Iohexol Clearance Survey in northern Europe,55 reported higher baseline prevalence of chronic kidney disease among women. However, men were more likely to progress to end-stage kidney disease or die from any cause, suggesting a slower rate of eGFR decline in women than men.…”
Section: Discussionmentioning
confidence: 96%